GAME ONLINE DAN AUTISITAS SOSIAL: STUDI KASUS GAMERS DOTA-2 MAHASIWA TEKNOLOGI INFORMASI UNIVERSITAS UDAYANA - Udiyani, Ni Putu; Nugroho, Wahyu Budi; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2016)
ABSTRACT Social Autisitas is a real form of gamers behavior that occurs as a result of the habit of playing online games DotA-2, which is also the repesentasi of hiperreality. Online game represents a new alternative space of influence of digitalization of modern life by using an intermediary media in the form of microcomputers which have internet access. DotA-2 is one of the most popular online games today, which is also one of the branches of international e-sport games, as well as an online game into the game in the activities of IT ESEGA by HMTI Udayana University. The habit of playing games bring positive or negative influence to the players which is can causing addiction. This study aims to understand the appeal of the game DotA-2, determine the intensity of the primary social interaction gamers DotA-2 Information Technology campus environment, and explain the behavior patterns of the gamers DotA-2 that leads to social autisitas behavior. This study was analyzed by using the concept of hyperreality of the theory of Jean P. Baudrillard's simulacra with qualitative descriptive method using structured interview method, observation and document analysis in data retrieval. This study shows the results of stating that the game DotA-2 is a type of role playing game with emphasis on strategy and teamwork. Keywords: Online Game, DotA-2 Players, Hyperreality, Social Autisitas